Enhanced photo-piezo-catalytic properties of Co-doped Ba0.85Ca0.15Zr0.1(Ti1-xCox)0.9 ferroelectric ceramics for dye degradation. Issue 5 (1st March 2023) - Zhao, Yan; Xu, Qianqian; Zhou, Xuefan; Yan, Mingyang; Gong, Hanyu; Yuan, Xi; Luo, Hang; Zhou, Kechao; Zhang, Dou; Bowen, Chris; Zhang, Yan
Abstract: This paper provides a detailed evaluation of the photo-piezo-catalytic properties of lead-free Ba0.85 Ca0.15 Zr0.1 (Ti1-x Cox )0.9 (BCZT- x Co, x  = 0–0.025) ferroelectric ceramics prepared by a solid-state process. By control of the Co doping level, the band gap was reduced to 2.40 eV at the composition x  = 0.02, which improved the generation of photo-generated charges and enhanced the photocatalytic activity. When a solution containing BCZT-0.02Co particles was subjected to both ultrasound and illumination, the degree of degradation of Rhodamine B reached 99% within 60 min, which was grater than when subjected to illumination or ultrasound alone. Examination of the dielectric properties, photoelectrochemical measurements and band energy structure of the materials provided new insights into the catalytic mechanism, where a strong coupling between piezoelectricity and photoexcitation was clearly observed. This work therefore highlights the attractive photo-piezo-catalytic properties of BCZT- x Co doped ceramics and is the first demonstration that Co substitution in these lead-free ferroelectric ceramics provides significant potential for photo-piezo-catalysis applications.